Avaliação do Índice de Maturação das Vértebras Cervicais em radiografias cefalométricas laterais, tomadas com diferentes posicionamentos de cabeça - Yamazaki, Marcos Shinao (2010)
This study aimed to evaluate the growth phase in a sample of 49 patients, with ages ranging from 9 to 15 years old, observing the cervical vertebrae on lateral radiographs taken in natural head position (NHP) and positioning errors, with head inclination up to 15° (NHP-High) and 15° down (NHP-Low), to define how important this is in the accuracy assessment phase of growth. The weighted kappa test showed a substantial degree of agreement between NHP and NHP High and between NHP and NHP-Low. Since the nonparametric test of wilcoxon (p <0.05) showed statistically significant difference between these comparisons. Thus, the NHP showed to be more reliable in assessing the cervical vertebrae maturation (CVM), furthermore the radiographs with positioning accuracy evaluated did not show statistically significant with the PNC.(AU)